A first insight into the genotoxicity induced on A549 human cell line by titanium and cerium dioxide nanoparticles co-exposed with arsenic and mercury - Vilaça, Cláudia (2021)
Objectives: Nanogenotoxicity studies traditionally consider exposure to a single NP. However, potential genotoxicity resulting from exposure to mixtures of NP and other contaminants cannot be neglected; This work will constitute the first insight into the DNA damage induced on A549 cells by exposure to binary mixtures of titanium (TiO2) and cerium (CeO2) dioxide, and highly toxic metals arsenic (As) and mercury (Hg).